Perceptions of Undergraduate Students on the Implementation of Oral Peer-feedback in Microteaching Classroom - Gina Larasaty; Nasir; Mochamad Reza (Universitas Sarjanawiyata Tamansiswa, 2022)
In teaching and learning, oral peer feedback has been used as an alternative learning strategy. Involving the students in the teaching and learning process can hopefully improve their skills, especially in improving their critical thinking. Studying this subject was challenging. This study purposed to find out the students’ perception of oral peer feedback in a microteaching classroom. This qualitative study was conducted in a descriptive case study design. 15 undergraduate students participated in this study. All of them were in the 7th semester of the English Education Department for the 2020/2021 academic year, Wiralodra University, Indramayu. To obtain the undergraduate students’ perceptions, the questionnaire was used to get data. The result of the research revealed that knowing what to do before conducting oral peer feedback helps a lot in peer commenting; providing oral peer feedback to my peers gives me new knowledge. Then, the students feel interested and challenged to conduct oral peer feedback. Moreover, the undergraduate students perceived oral peer feedback as having many benefits, such as increasing their teaching skills, helping them manage the class and time, and also helping them how to communicate with students. This study can also be used as a guide for oral peer- feedback in the Micro teaching classroom.